(untitled) (Itinera, 2024)
This article aims to analyze how the drone - in its prosthetic, machine and automated dimension - and the operative images that emerge from the recording of certain sites intervened with war and extractivist motives generate ecomedial and techno-imaginary ecologies of seemingly uninhabited territories. The above is developed from the analysis of two audiovisual projects: The Landmine Project (2016-2020) by the Chilean collective Agencia de Borde and Prelude To: When The Dust Unsettles by Dutch artist and designer Femke Herregraven (2022). The former explores minefields laid between 1973 and 1983 in the Atacama Desert in Chile, while the latter shows the modus operandi of a digital twin for mining in the Congo. These are seemingly untouchable territories, out of circulation, where, given their imagined future - either as explosive or exploited territory - a drone and its digital eye appear to be the only way to visually access these places, which are presented as inadmissible and uninhabited. Both cases expose geopolitical conflicts that are primarily articulated and mediated through the production and manipulation of images and technical intervention. In this way, the development of the text proposes to think about forms of contemporary violence that take shape through specific visual devices and rhetorics.